INTERIOR DESIGN OF SURABAYA ARTS and CULTURAL THEATRE - naniek indriani (Saraswati)
Surabaya Arts and Cultural Theater is a building constructed on top of the old ruins situated among the old colonial era buildings in Surabaya with their Dutch colonial architectural styles. The building was previously a movie theaterbefore its demolition for the purpose of new building construction project. During the colonial era the building was the place where the Dutch met to engage in pool billiard sports during their leisure times. Right now the building has beenrevamped as the Surabaya Arts and Cultural Theatre.As an arts and cultural center, the building is equipped with various supporting facilities which may reflect and present the true culture of East Java. It should be able to accommodate the inspirations of all local artists. The arts and cultural theater is a building with classifications, facilities, and certain requirements in which it should be able to meet the demands to introduce the unique characteristics, arts, and cultures of the region in which the building is situated.The interior design of Surabaya Arts and Cultural Theater include the lobby area, auditorium, art gallery, coffee shop, changing/dressing room, and toilet which carries the "Sparkling Surabaya" theme with its Post-Modern style. The concept above is expected to enhance the image and bring a new atmosphere for other cultural centers in East Java as well, with particularemphasis on Surabaya Arts and Cultural Theater.